SELF-EFFICACY AND MOTIVATION CONSTRUCT: AN INSTRUMENT DEVELOPMENT - Marisa Yoestara; Zaiyana Putri; Nyak Mutia Ismail; Meta Keumala (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
This study aims to develop a questionnaire as the valid and reliable instrument to measure the students’ self-efficacy and motivation in learning English. The development process in this study was based on the theory of the two main constructs (self-efficacy and motivation). The writers employ cognitive interview to create some adjustment and/or adaptation to fit the Indonesian learning and process context, and pilot tested to a group of students. The product of this study is a ready-to-use questionnaire that is considered appropriate in Indonesian context. Further research is suggested to check the validity and reliability of thisinstrument in other contexts.